The Economics of Big Science 2.0 Essays by Leading Scientists and Policymakers - Gutleber, Johannes; Charitos, Panagiotis; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
The second volume of open access essays builds upon the success of the initial installment, "The Economics of Big Science (© 2021, 978-3-030-52390-9, Open Access book as well)," delving deeper into the tangible socio-economic value generated by fundamental science missions and elucidating the various ways in which this benefit is realized. This collection showcases contributions that stem from socio-economic impact studies conducted on the activities of Research Infrastructures. These studies were presented and discussed by the authors during a dedicated session on the "Economics of Big Science" at the headquarters of the European Space Agency (ESA) in Paris in May 2023, organized by EIROforum. The authors, affiliated with prominent universities, research centers, and international research organizations, actively contribute to an international collaborative effort. Their aim is to develop strategies and policies that ensure fundamental scientific research in Europe translates into tangible and sustainable societal and economic benefits. This volume is intended to be a valuable resource for policymakers, funding agencies, scientists, and academics across diverse domains. It serves as a comprehensive reference for the evidence of socio-economic impact stemming from fundamental scientific research within Open Science, Research, and Innovation environments. Moreover, it equips stakeholders with evidence supporting the effectiveness of impact analysis and facilitates the design of best practices in this regard.
Socio Economic Impact Assessment of ESA Programmes -- Observation, Analysis and Evaluation of the Industrial Contribution to the Peer Reviewed Public Access of the ESRF: A Pilot Study -- Large scale research infrastructures contributions to local economy: A pilot survey -- The value of Open Science at CERN: An analysis based on a travel cost model -- The regional impact of single site and distributed research infrastructures using the example of DORIS and CTAO -- Social Licence to Operate: A Critical Success Factor in Realising Impact from Research Infrastructure -- Awareness and attitudes towards science. The case of CERN -- Thinking how to define and measure impacts of RIs -- Costs and benefits of Open Science: contributing to developing a rigorous assessment framework -- From science to society: the Open Science & Innovation & Network approach -- How to measure the local economic impact of Large Research Infrastructure procurement -- From the National Laboratory to International Collaborations (Framing Big Science for the Age of Science Diplomacy) -- Estimating the FCC'S short-term Impact on Value Added and Employment - an Input Output Analysis -- The value of a collaborative platform in a global project -- The value of an open scientific data and documentation platform in a global project: The case of Zenodo.
Keywords: Nuclear physics; Economic development; Valuation; Artificial intelligence -- Data processing; Solar system; Measurement; Measuring instruments; Nuclear and Particle Physics; Economic Development, Innovation and Growth; Investment Appraisal; Data Science; Space Physics; Measurement Science and Instrumentation